Pengaruh Konversi Lahan Terhadap Strategi nafkah Rumah Tangga Petani - Pratiwi, Andini Wulan; Murdianto, Murdianto (Jurnal Sains Komunikasi dan Pengembangan Masyarakat [JSKPM], 2019)
Land conversion is a phenomenon of the use of agricultural to non agricultural. This phenomenon appears cause the increase growth of suburban population and the demand for land. It can brings the impact for the community to decrease farmer’s income, the lowering of family food security, the subside employment oppurtunities in agriculture, and the difficulties farmer’s access to land. The farmer in improving household economy do a livelihood strategy that is diversification of livelihood, circular migration, and the transition of livelihood. This paper aim to examine the factors that encourage land conversion and to examine farmer’s livelihood strategies due to land conversion. The method used in this research is quantitive approach with the main instrument questionnaire supported by qualitative approach with in-depth interviews. The results of the research in Palasari village indicate that there are aspects that encourage land conversion in the form of urgent economic needs, low land productivity, external pressure, and knowledge aspects owned by farmers regarding government policy. In addition, for most farmers who have converted agricultural land prefer to switch livelihoods to other sectors. Livelihood transition occurs due to the increasingly narrow land of their farms.Keywords : farm households, land conversion, livelihood strategies ABSTRAK Konversi lahan merupakan suatu fenomena pemanfaatan lahan terhadap lahan pertanian menjadi non pertanian. Fenomena ini muncul disebabkan pertumbuhan penduduk pinggiran kota yang semakin tinggi serta tingginya permintaan terhadap lahan. Hal tersebut tentunya dapat memberikan dampak kepada masyarakat terhadap penurunan pendapatan petani. Petani dalam meningkatkan ekonomi rumah tangga melakukan strategi nafkah yaitu diversifikasi nafkah, migrasi sirkuler, dan peralihan mata pencaharian. Tujuan penelitian ini untuk mengkaji faktor-faktor yang mendorong terjadinya konversi lahan serta mengkaji strategi nafkah rumah tangga petani akibat adanya konversi lahan. Metode yang digunakan yaitu pendekatan kuantitatif dengan kuesioner dan didukung oleh data kualitatif dengan wawancara. Hasil penelitian di Desa Palasari menunjukkan bahwa terdapat aspek-aspek yang mendorong terjadinya konversi lahan berupa kebutuhan ekonomi yang mendesak, produktivitas lahan, tekanan pihak luar, dan aspek pengetahuan petani. Sebagian besar petani yang telah mengkonversi lahan pertaniannya lebih memilih untuk beralih mata pencaharian ke sektor lain. Peralihan mata pencaharian terjadi disebabkan oleh luas lahan pertanian mereka yang semakin sempit.Kata Kunci : konversi lahan, rumah tangga petani, strategi nafkah